Unfolding intersecting forms of socio-spatial exclusion: Accommodation centres at the height of the “refugee reception crisis” in Germany - Shahd Seethaler-Wari; Zeynep Yanasmayan (International Migration, 2023)
At the height of the “refugee reception crisis” in 2015, a large number of forced migrants had to be accommodated in Germany, which led to the transformation of old infrastructures and building of new centres. Based on extensive fieldwork in three centres in the same city, this article seeks to highlight the intersecting forms of socio-spatial exclusion in refugee accommodations in Germany. First, we unpack how differential internal and external spatial arrangements intersect to aggravate or alleviate social exclusion of forced migrants. Second, we draw attention to the ways in which the regulation of space and social relations inside the accommodation centres intersect with the dominant gendered notions of the refugee label. Despite the potency of power relations that differentially categorizes, controls and excludes, exclusion remains ambivalent as forced migrants consistently claim ownership over the space in and around the centres and build social relationships to maintain a sense of “normalcy”.
Keywords: 300